2021
DOI: 10.1039/d0nj05285j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot access to sulfonylated naphthalenediols/hydroquinones from naphthols/phenols with sodium sulfinates in an aqueous medium

Abstract: A metal-free method towards sulfonylated hydroquinones/naphthalenediols under an ambient atmosphere has been developed with up to 97% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In 2017, Wu [8] and co‐workers developed a Cu and Mn synergistic catalytic strategy for the sulfonation of arylquinones with sulfonyl hydrazides as the sulfone source (Scheme 2b). Recently, a one‐pot method for the synthesis of sulfonylated hydroquinones/ naphthalenediols employing hypervalent iodine as the oxidizing agents have been reported by Reheman and Chen's groups (Scheme 2c) [9] . However, these methods have obvious drawbacks, including the use of transition metals, strong oxidants, and harsh acidic treatments, which makes them environmentally unfriendly and poorly functional group compatible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Wu [8] and co‐workers developed a Cu and Mn synergistic catalytic strategy for the sulfonation of arylquinones with sulfonyl hydrazides as the sulfone source (Scheme 2b). Recently, a one‐pot method for the synthesis of sulfonylated hydroquinones/ naphthalenediols employing hypervalent iodine as the oxidizing agents have been reported by Reheman and Chen's groups (Scheme 2c) [9] . However, these methods have obvious drawbacks, including the use of transition metals, strong oxidants, and harsh acidic treatments, which makes them environmentally unfriendly and poorly functional group compatible.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a one-pot method for the synthesis of sulfonylated hydroquinones/ naphthalenediols employing hypervalent iodine as the oxidizing agents have been reported by Reheman and Chen's groups (Scheme 2c). [9] However, these methods have obvious drawbacks, including the use of transition metals, strong oxidants, and harsh acidic treatments, which makes them environmentally unfriendly and poorly functional group compatible. Therefore, it is essential to develop a facile, highly efficient, and greener approach to constructing sulfonylated hydroquinones.…”
mentioning
confidence: 99%
“…in 2021 reported a simple, one‐pot and transition metal‐free methodology for sulphonylation of numerous phenols and naphthols to afford corresponding sulphonylated hydroquinones and sulphonylatednaphthalenediols in moderate to excellent yields using low‐cost and easily available sodium sulphinates as the sulphonylation reagent and PIFA (Scheme 45) and PIDA (Scheme 46) as oxidants in aqueous medium. It was found that best result of 97% yield was obtained when sodium 4‐methylbenzenesulfinate was used as the sulphonylating reagent [93] …”
Section: α‐Functionalization Reactionsmentioning
confidence: 99%
“…It was found that best result of 97% yield was obtained when sodium 4-methylbenzenesulfinate was used as the sulphonylating reagent. [93] 7. α, β-Bifunctionalization Reactions bromosuccimide (NBS) as the nitrogen and bromine sources, respectively (Scheme 47). This aqueous reaction, apart from promising a clean and eco-friendly reaction condition, permits the aminobromination of olefins to proceed smoothly and effectively.…”
Section: α-Sulfonylation Reactionsmentioning
confidence: 99%